Efectos del consumo de leche bubalina con alto contenido de grasas trans en la degeneración grasa hepática inducida por colesterol en conejos - Lertora,W.J. (2019)
This work compared the effects of the two bubaline milk consumption, with low and high ratio of tFA/SFA, on lipemia and the development of hepatic fat degeneration induced by cholesterol in rabbits. Twenty New Zealand males rabbits were randomly separated into a control group (n=10) that received milk with low trans/saturated FA ratio (5.3% tFA and 67.12% SFA) obtained from grazing buffalos; and a high trans group (n=10) that received milk with high tFA/SFA ratio (25.84% tFA and 45.89% SFA) obtained from buffalos with lipid supplementation in their diet. The milk was administered for 75 days and its intake was recorded daily. From day 15, all rabbits were challenged with 0.93 g of cholesterol/day, orally, in order to induce hepatic fat degeneration. The serum lipidogram, ALT and AST were recorded. On the liver, lipid content, sudanophilic area, fibrosis and macrophage infiltration were evaluated. The rabbits voluntarily consumed 9293.13 ml and 9930 ml of milk with low and high tFA/SFA ratio, respectively, without difference between groups (p 0.404). Rabbits in high trans group registered higher serum levels of total cholesterol than the control group (6.08 vs. 5.58 g/l, p 0.049). The ALT were significantly (p <0.0001) higher in the high trans group than the control group. The liver lipids recorded a significant (p 0.0437) increase in the high trans group (10.62%) when it was compared to the control (8.68%).The high trans group recorded a greater extension of the sudanophilic area (37.05 ± 7.53% vs. 26.42 ± 12.55%, p 0.0338), a greater frequency of fibrosis (8 vs. 3 livers, p 0.0247) and more infiltration of macrophages in hepatic parenchyma (94.20 vs. 48 macrophages, p 0.0190) than the control group. In conclusion, milk with high tFA/SFA ratio contributed to increase total cholesterol levels and to increase the hepatotoxic effect of cholesterol, when was compared with milk with a low ratio of tFA/SFA. These effects are possibly related to the tFA content of this milk.